Science Collaboration for Capacity Building: Advancing Technology Transfer Through a Treaty for Biodiversity Beyond National Jurisdiction - Harden-Davies, Harriet; Snelgrove, Paul (Frontiers in Marine Science, 2020)
Marine technology transfer and capacity building are key elements in the development of a historic new agreement for the conservation and sustainable use of marine biodiversity in areas beyond national jurisdiction (BBNJ agreement) under the United Nations Convention on the Law of the Sea (UNCLOS). This vast, deep ocean area remains largely unexplored and poorly understood. Scientific knowledge gaps impede informed decision-making, and most countries lack the capacity to participate in ocean science activities in ABNJ or to benefit from discoveries of new ocean life, habitats, and processes. Consequently, science must play a central role in capacity building aspirations, however, the link between technology transfer and marine scientific research has yet to be examined in depth. Here, we examine the UNCLOS framework for marine technology transfer and highlight linkages with marine scientific research, identifying four key themes for capacity building: access to data, information and knowledge; equipment; training; and collaboration. We provide examples to illustrate current practices and identify gaps in implementation. We show that marine technology transfer and marine scientific research inherently link in principle and in practice. We propose measures for the BBNJ agreement to strengthen the international framework for the transfer of marine technology in order to boost marine scientific research collaboration, fill knowledge gaps, and strengthen capacity through inclusive international participation.